Nanoscopical Analysis Reveals an Orderly Arrangement of the Presynaptic Scaffold Protein Bassoon at the Golgi-Apparatus - Ghelani, Tina; Montenegro-Venegas, Carolina; Fejtova, Anna; Dresbach, Thomas (Frontiers in Molecular Neuroscience, 2021)
Bassoon is a core scaffold protein of the presynaptic active zone. In brain synapses, the C-terminus of Bassoon is oriented toward the plasma membrane and its N-terminus oriented towards synaptic vesicles. At the Golgi-apparatus Bassoon is thought to assemble active zone precursor structures, but whether it is arranged in an orderly fashion is unknown. Understanding the topology of this large scaffold protein is important for models of active zone biogenesis. Using stimulated emission depletion nanoscopy in cultured hippocampal neurons, we found that an N-terminal intramolecular tag of recombinant Bassoon, but not C-terminal tag, colocalized with markers of the trans-Golgi network (TGN). The N-terminus of Bassoon was located between 48 nm and 69 nm away from TGN38, while its C-terminus was located between 100 nm and 115 nm away from TGN38. Sequences within the first 95 amino acids of Bassoon were required for this arrangement. Our results indicate that at the Golgi-apparatus Bassoon is oriented with its N-terminus towards and its C-terminus away from the trans-Golgi network membrane. Moreover, they suggest that Bassoon is an extended molecule at the trans-Golgi network with the distance between amino acids 97 and 3938 estimated to be between 46 and 52 nm. Our data are consistent with a model, in which the N-terminus of Bassoon binds to the membranes of the trans-Golgi network, while the C-terminus associates with active zone components, thus reflecting the topographic arrangement characteristic of synapses also at the Golgi-apparatus